Sevoflurane Inhibits the Th2 Response and NLRP3 Expression in Murine Allergic Airway Inflammation - Lixia Wang; Binshan Zha; Qiying Shen; Hongyun Zou; Cheng Cheng; Huimei Wu; Rongyu Liu (Journal of Immunology Research)
Background. Our colleagues have demonstrated an impressive therapeutic role of sevoflurane in a murine allergic airway inflammation model, but the mechanisms underlying this effect remain undefined. In this study, we tried to investigate the effect of sevoflurane on the resolution of allergic airway inflammation and to assess whether NLRP3 or the NLRP3 inflammasome is involved in this process. Methods. Female (C57BL/6) mice were sensitized and challenged with ovalbumin (OVA). Then, some of the mice received MCC950 (10 mg/kg; i.p.) or 3% sevoflurane. Total and differential inflammatory cell numbers, proinflammatory cytokines in bronchoalveolar lavage fluid (BALF), the peribronchial inflammation density, and mucus production were evaluated. In addition, we analysed the protein levels of NLRP3, the apoptosis-associated speck-like protein containing the caspase activation and recruitment domain (ASC), pro-caspase-1, and caspase-1 in the lung tissue. Results. We found that OVA-induced inflammatory cell recruitment to peribronchial regions, goblet cell hyperplasia, the serum levels of IgE, inflammatory cells, and the Th2 cytokine secretion in BALF was potently suppressed by sevoflurane with an efficacy comparable with that suppressed by MCC950 treatment. Furthermore, sevoflurane, similar to MCC950, clearly inhibited the OVA-induced activity of NLRP3 in the lungs. In addition, we found that OVA challenge failed to increase the expression of ASC, pro-caspase-1, and caspase-1 in the lungs and the levels of IL-18 and IL-1β in BALF. Conclusion. Taken together, our data showed that sevoflurane ameliorated allergic airway inflammation by inhibiting Th2 responses and NLRP3 expression. The NLRP3 independent of inflammasomes participated in the pathogenesis of allergic asthma in this model.